Evaluation of a quasi-passive biarticular prosthesis to replicate gastrocnemius function in transtibial amputee gait. (2nd December 2021) - Willson, Andrea M.; Richburg, Chris A.; Anderson, Anthony J.; Muir, Brittney C.; Czerniecki, Joseph; Steele, Katherine M.; Aubin, Patrick M.
Abstract: Lower limb amputees experience gait impairments, in part due to limitations of prosthetic limbs and the lack of a functioning biarticular gastrocnemius (GAS) muscle. Energy storing prosthetic feet restore the function of the soleus, but not GAS. We propose a transtibial prosthesis that implements a spring mechanism to replicate the GAS. A prototype Biarticular Prosthesis (BP) was tested on seven participants with unilateral transtibial amputation. Participants walked on an instrumented treadmill with motion capture, first using their prescribed prosthesis, then with the BP in four different spring stiffness conditions. A custom OpenSim musculoskeletal model, including the BP, was used to estimate kinematics, joint torques, and muscle forces. Kinematic symmetry was evaluated by comparing the amputated and intact angles of the ankle, knee, and hip. The BP knee and ankle torques were compared to the intact GAS. Finally, work done by the BP spring was calculated at the ankle and knee. There were no significant differences between conditions in kinematic symmetry, indicating that the BP performs similarly to prescribed prostheses. When comparing the BP torques to intact GAS, higher spring stiffness better approximated peak GAS torques, but those peaks occurred earlier in the gait cycle. The BP spring did positive work on the knee joint and negative work on the ankle joint, and this work increased as BP spring stiffness increased. The BP has the potential to improve amputee gait compensations associated with the lack of biarticular GAS function, which may reduce their walking effort and improve quality of life.